Building an App UI with PrimeFaces - Du Toit, Kobus; Safari eBooks ([S.l.] : Packt Pub., 2014)
"Packt video courses are designed to cover the breadth of the topic in short, hands-on, task-based videos. Each course is divided into short manageable sections, so you can watch the whole thing or jump to the bit you need. The focus is on practical instructions and screencasts showing you how to get the job done. This is a comfortably-paced video tutorial that starts off with the basic concepts and gradually picks up speed by integrating PrimeFaces with a range of other software to develop a website with an attractive interface and advanced features. If you know Java and want to develop great looking UIs for your web applications using PrimeFaces, then this tutorial is just for you. You do not need any previous web or database experience."--Resource description page.
Title from title screen (viewed Aug. 22, 2014).
Presenter, Kobus du Toit.
Keywords: MongoDB; User interfaces (Computer systems); Application software -- Development; WEB (Computer program language); Web sites -- Development; Web sites -- Design; Electronic books